2021
DOI: 10.1007/s12560-021-09481-1
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Processes for Water and Wastewater Viral Disinfection. A Systematic Review

Abstract: Water and wastewater virological quality is a significant public health issue. Viral agents include emerging and re-emerging pathogens characterized by extremely small size, and high environmental stability. Since the mainly used conventional disinfection methods are usually not able to achieve complete disinfection of viral and other microbial targets, in real water and wastewater matrices, effective strategies for the treatment, use and reuse of water and the development of next-generation water supply syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…The higher TOF was achieved with a smaller amount on the active catalytic site [ 78 ]. Interestingly, the synergic effect between active nanoparticles and the support leads to better reusability and recyclability [ 79 , 80 , 81 ].…”
Section: Metal and Metal Oxide Nanoparticles In Aopsmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher TOF was achieved with a smaller amount on the active catalytic site [ 78 ]. Interestingly, the synergic effect between active nanoparticles and the support leads to better reusability and recyclability [ 79 , 80 , 81 ].…”
Section: Metal and Metal Oxide Nanoparticles In Aopsmentioning
confidence: 99%
“…The metal-to-clay ratio determines much of the catalytic and photocatalytic activity, governing the physicochemical character of pillared clay. From many studies, such as research on the synthesis of TiO 2 -pillared montmorillonite and SnO 2 -pillared montmorillonite, it can be concluded that the metal-to-clay ratio is not linearly correlated with increasing either the physical characteristics or the catalytic performance of the pillared clay, but it has an optimum condition, which depends on the electronic properties of the surface, the cation exchange capacity of clay, and the affinity of metal polyoxocations to enter the intercalating region [ 80 , 144 ]. Figure 9 presents the effect of the metal:clay ratio on the d 001 of pillared clays, indicating the optimum conditions.…”
Section: Clay Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…( Teymoorian et al, 2021 ; Hasani et al, 2021 ). Advanced oxidation processes (AOPs) are highly advanced technology that generates oxidative and reductive agents like hydroxyl radicles to treat toxic pathogens ( Nasir et al, 2021 ; Kokkinos et al, 2021 ). Generated reactive radicles directly and effectively deteriorate the viruses.…”
Section: Introductionmentioning
confidence: 99%